2011
DOI: 10.1038/kisup.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and bone disorders in chronic kidney disease and end-stage renal disease patients: new insights into vitamin D receptor activation

Abstract: Progressive loss of kidney function leads to reduced production of calcitriol (1,25-dihydroxyvitamin D; active vitamin D) and an imbalance in serum calcium (Ca) and phosphorus (P) levels, which are associated with progression of renal failure as well as increased rates of cardiovascular (CV) events and mortality. In addition, multifactorial hypocalcemia and resistance to parathyroid hormone (PTH) can lead to prolonged and excessive synthesis and secretion of PTH, eventually leading to development of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 107 publications
(160 reference statements)
0
22
0
2
Order By: Relevance
“…The extra-renal expression of CYP27B1, CYP24A1 and vitamin D receptor (VDR) is considered the cornerstone of vitamin D's pleiotropic effects [13] . VDR is a ubiquitous nuclear receptor, with a major genomic regulatory effect, currently considered a crucial modulator of the human genome.…”
Section: Vitamin D System: Pathophysiologymentioning
confidence: 99%
“…The extra-renal expression of CYP27B1, CYP24A1 and vitamin D receptor (VDR) is considered the cornerstone of vitamin D's pleiotropic effects [13] . VDR is a ubiquitous nuclear receptor, with a major genomic regulatory effect, currently considered a crucial modulator of the human genome.…”
Section: Vitamin D System: Pathophysiologymentioning
confidence: 99%
“…107 Histomorphometric studies performed 2 years after transplantation revealed mineralization defects as well as higher osteoid, osteoblastic, resorption, and osteoclastic surfaces, indicative of persistent hyperparathyroidism that can be attributed at least in part to hypovitaminosis D. 107 Hyporesponsiveness of the bone to PTH in patients with CKD is caused by phosphate loading, decreased calcitriol, antagonistic PTH fragments, downregulation of PTH receptors, and decreased pulsatile secretion of PTH. 108 Some of the bone abnormalities induced by persistent hyperparathyroidism after kidney transplantation might, therefore, be explained by the removal of skeletal resistance to PTH, as most of the aforementioned factors are restored and elicit an important bone response to PTH. The bone response to PTH might also be enhanced by gluco corticoid treatment, as shown in vitro.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…Progressive loss of kidney function is linked to a reduction in the production of vitamin D and to a disturbance in serum calcium and phosphorus balance that have been associated with poor CKD outcome and to increased risk for CVD events and mortality [74].…”
Section: Other Markersmentioning
confidence: 99%